Pemberdayaan Pada Ibu Tentang Anticipatory Guidance - Dyah Siwi Hety; Citra Adityarini Safitri (Jurnal Pengabdian Masyarakat, 2026)
Providing anticipatory guidance is a crucial step for parents in understanding the various risks that arise during each phase of a child’s growth and development. A lack of understanding in this area often makes it difficult for mothers to respond to the challenges of their toddlers’ growth and development. This study aims to improve mothers’ knowledge and change their attitudes and behaviors regarding the provision of guidance and advice on health issues at each stage of their children’s development. The methods used in this program included health education and intensive training on anticipatory guidance strategies. Participants were mothers of toddlers in the service area of the relevant community health center. Evaluation was conducted by comparing mothers’ knowledge levels before and after the intervention. The results showed that the majority of participants—50%—had a high level of education. The post-intervention evaluation revealed a 20% increase in the knowledge scores of mothers of toddlers compared to before the intervention. This indicates that the education and training methods were highly effective in improving parents’ understanding of the importance of anticipatory guidance. In conclusion, improving mothers’ knowledge is a key factor in improving parenting behaviors. It is hoped that this activity can serve as a sustainable step toward minimizing child development issues through the active role of parents within the family environment.